Pengaruh Kualitas Pelayanan dan Nilai Nasabah Terhadap Kepuasan Nasabah Pada PT. Bank BPD Bali Capem Unud - Sari, Anak Agung Ayu Ratih Permata; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
The development of banking business has been growing rapidly. Customer satisfaction is an important thing that is maintained by the bank as it pertains to the success of a value of the service provided. The purpose  determined the effects of servquals and customer value on customer satisfaction’s Bank BPD Bali Capem Unud. This study used a propotionate random sampling’s method, with a sample size of 100 respondents. This study found that a significant and positive effect on customer satisfaction between service quality and customer value. PT. Bank BPD Bali Capem Unud suggested to improve the qualities of serviced and value for its customers to be able to retain customers and strengthen their image. Keywords: service quality, customer value and customer satisfaction.
Keywords: service quality, customer value and customer satisfaction